Análise multitemporal da linha de costa da ilha de Algodoal/Maiandeua, município de Maracanã/PA - ALVES, Gabriel Silveira da Silva (2019)
Changes in the coastline are triggered by natural or anthropogenic processes and act at different temporal and spatial scales, with direct responses to the policies employed by coastal cities dependent of the use of the coast for economy, tourism or recreation. The paraense salty zone is within the area of hydrological influence and the sedimentary contribution of the Amazon River, having a constant variation in its coastline, either by erosion or accretion of sediments. The Algodoal/Maiandeua Island, municipality of Maracanã, present in the salty zone, undergoes the natural dynamics of the morphology of coastal environments what can cause damage to the resident population in the place. The objective of this work is to identify the areas of accretion and coastal erosion and calculate these variations on the sandy beaches of the four communities of the island (Algodoal, Fortalezinha, Mocoóca and Camboinha) during 28 years (1988-2016); To this end, satellite images made available by the United States Geological Survey (USGS) using ArcGIS software and its Digital Shoreline Analysis System (DSAS) extension, which statistically computes the variations of the coastline through a time series. The island presented a more stable area with average variations between 1 and 2 m/year, for both advancement and costal retreat, in its western portion (Algodoal and Camboinha villages) while to the east were identified great variations, especially in the beaches of Fortalezinha and Princesa, where a great advance of the coast line could be observed, with averages up to 16 m/year of advance and 8 m/year of recoil. In general, the DSAS functions is a practical tool with quick results that can be used to visualize long-term morphological changes and without the need for physical measurements in situ, however, for a more complete result of characterization of the study area, such measurements are of paramount importance, especially for the provision of future estimates of variations in the coastline.